Biotyping of Arcobacter butzleri isolated from poultry products: rescuing a phenotypic method - Heriberto Fernández; Karen Ringler; María Laura Arias (Bioscience Journal, 2016)
Arcobacter butzleri is an emergent zoonotic foodborne pathogen associated to enteritis and occasionally to bacteremia in human beings. Biotyping of this bacterium is important in order to establish the circulating strains and its dissemination routes. The purpose of this work was to determine the circulating A. butzleri biotypes in poultry products for human consumption in Southern Chile using the method proposed by Lior and Woodward, in order to explore the possibility of introducing this biotyping scheme as a routine laboratory tool. From the 60 strains studied the prevalent biotypes were 8A, 8B, 7A, 4A and 4B. The most frequently isolated biotype, independently of the sample of origin, was 8A with (44 strains, 73.3%). The less frequently isolated biotype was 4B (two strains 3.3%).